Impact of Intraoperative Cone Beam Computed Tomography on Reduction Quality and Implant Position in Treatment of Tibial Plafond Fractures. (September 2016) - Vetter, Sven Yves; Euler, Finn; von Recum, Jan; Wendl, Klaus; Grützner, Paul Alfred; Franke, Jochen
Background: The intraoperative assessment of the articular surface in displaced intra-articular distal tibia fractures can be challenging using conventional fluoroscopy. The aim of the study was to determine the frequency and the method of intraoperative corrections of fracture reductions or implant placements during open reduction, internal fixation by using cone beam computed tomography (CT) after conventional fluoroscopy. Methods: Displaced intra-articular distal tibia fractures were retrospectively analyzed from August 2001 until December 2011. The fractures were classified according to the standards of the AO/OTA as type B or C and treated with open reduction and internal plate fixation. After primary reduction using conventional fluoroscopy, an additional cone beam CT scan was used to determine the alignment of the joint line and the implant position. The number of intraoperative revisions of the primary reduction due to the use of cone beam CT was analyzed. Results: A total of 143 patients with an intra-articular tibial plafond fracture were included in the analysis. In 43 patients (30%), an intraoperative correction was performed after the cone beam CT scan. In 34 (24%) of these cases, intraoperative correction was required because of inadequate joint line reduction. Nine (6%) corrections were required as a result of a malposition of the implant. The revision rate did not differ by fracture classification. Conclusion: Despite its acceptance as the standard method of imaging, intraoperative conventional fluoroscopy for the assessment of implant positioning and fracture reduction of tibial plafond fractures is limited. The intraoperative utilization of cone beam CT provided additional information for the surgeon to detect insufficient reduction or implant malposition. Level of Evidence: Level III, retrospective comparative series.